Study of ergonomics in terms of angle of manipulation and angle of azimuth in laparoscopic splenectomy - Joshi, Gaurav; Baig, Khaja Abdul Moin; Chaturvedi, Aparajita; Jayaram, Jnaneshwari; Rathore, Yashvant S.; Chumber, Sunil (International Surgery Journal, 2021)
As per baseball diamond concept of port position, experimentally it is well known that putting camera port in the line of target organ and working port equidistant from camera port such that they form a 30º angle each gives optimum ergonomic advantage. However while performing laparoscopic surgeries in humans it is seldom possible to achieve such port position. No such study has ever been attempted to find out value of angle of manipulation and angle of azimuth while performing laparoscopic procedure. Purpose of our study was to measure such angles in our patients during laparoscopic splenectomy (LS) and to verify the concept of baseball position of ports in the procedure. This was a prospective observational study where angle of manipulation between right and left working port of surgeon and angle of azimuth of both working instruments with the camera were measured intraoperatively. In our series of 12 patients who underwent LS in lateral position, we found angle of manipulation ranging from 41-85°. The azimuth angle between first working port (epigastric) and camera port was in the range of 22-45° and the azimuth angle between camera port and second working port was in the range of 19-40°. This was a first study that gave valuable insight into the application of theoretical concept of triangulation in port placement in LS. This study may guide the surgeons to measure and to modify the port position to gain advantage of better ergonomics and better long term health.